The Effectiveness of Mathematics Teaching Materials on Problem Solving Ability in Junior High School Students - Yuniar Rohmatun Nisa; Risma Amelia (IKIP Siliwangi, 2021)
Mathematics learning aims to develop all student’s mathematical abilities in obtaining good mathematics learning outcomes maximum. The important target in achieving these learning outcomes is by maximizing learning on problem-solving ability. Accordingly, the purposes of this research were to know how the implementation of mathematics teaching materials on problem-solving ability and to know the categories of the effectiveness of mathematics teaching materials on problem-solving ability. The research method used in this research is descriptive which was obtained from observation, questionnaires, and tests. The participants of this study were students of the seventh grade of Junior High School which consists of two classes. The results informed that there were three kinds of effectiveness, that is interaction effectiveness which showed 55% less effective category, effectiveness of understanding which showed 61.8 % quite effective category, the effectiveness of teaching materials on problem-solving abilities which showed 52.78 % less effective category. Furthermore, appropriate learning materials and the creativity of the teacher in delivering learning materials are considered to be implemented in the mathematic learning process.